Effect of Peganum harmala seeds on productive performance, immune responses and liver function in broiler chickens - GOODARZI, MAJID; NANEKARANI, SHAHRAM (The Indian Journal of Animal Sciences, 2015)
This experiment was designed to study the effects of feeding different levels of Peganum harmala seeds (PHS) and antibiotic on the performance, immune responses and liver function of Ross broiler chickens. A total of 240 one-d-old unsexed broiler chickens were randomly allocated to each of the 4 treatment groups, each with 4 replicate pens of 15 chicks. The dietary treatments included of control (C) - without PHS and antibiotic - the diet contains 300 mg/Kg Lincomycin 0.88% (A) and the diets contain 20g/kg (H1) and 40g/kg (H2) PHS. The performance parameters were measured during the experimental period. The chicks were raised on floor pens and received diets and water ad libitum for 6 weeks. Blood samplings were performed for determine of antibody titer against Newcastle disease virus (NDV) on 14 and 21 days and for liver function test on 42 days of age. The using of PHS at rate of 20g/kg feed improved some traits such as live body weight and FCR, but the consumption of 40g/kg had undesirable effect on these traits. Antibody titer against NDV was not affected by experimental treatments, but the relative weight of bursa and spleen increased by dietary treatments of antibiotic and H2. Broilers receiving 40g/kg PHS had a significantly higher activity of SGOT, SGPT and SALP in serum compared to control group. It can be concluded that Peganum harmala seeds cannot be applied as alternatives to in-feed antibiotics, but 20 g/kg inclusion of it in diet can improve production efficiency of broiler chickens.